2022
DOI: 10.3390/curroncol29100622
|View full text |Cite
|
Sign up to set email alerts
|

Boron Neutron Capture Therapy: Clinical Application and Research Progress

Abstract: Boron neutron capture therapy (BNCT) is a binary modality that is used to treat a variety of malignancies, using neutrons to irradiate boron-10 (10B) nuclei that have entered tumor cells to produce highly linear energy transfer (LET) alpha particles and recoil 7Li nuclei (10B [n, α] 7Li). Therefore, the most important part in BNCT is to selectively deliver a large number of 10B to tumor cells and only a small amount to normal tissue. So far, BNCT has been used in more than 2000 cases worldwide, and the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“… 106 Although preliminary clinical results of BNCT are promising, further research is needed in order to find more selective boron compounds. 107 …”
Section: Novel Lines Of Research In Glioblastoma and Gliomas In Generalmentioning
confidence: 99%
“… 106 Although preliminary clinical results of BNCT are promising, further research is needed in order to find more selective boron compounds. 107 …”
Section: Novel Lines Of Research In Glioblastoma and Gliomas In Generalmentioning
confidence: 99%
“…Locher (1936) proposed the concept of neutron capture therapy in the mid‐1930s, but only after the end of the Second World War, the development of nuclear reactors for medicine allowed to start clinical trials of BNCT (Jin et al, 2022). Although the clinical trials showed the promising results, there is a number of limitations to the widespread use of BNCT technology (Cheng et al, 2022; Jin et al, 2022). Achieving optimal boron concentrations in tumor cells, normal tissue, and blood is the most important problem in the BNCT (Cheng et al, 2022; Sauerwein et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical trials showed the promising results, there is a number of limitations to the widespread use of BNCT technology (Cheng et al, 2022; Jin et al, 2022). Achieving optimal boron concentrations in tumor cells, normal tissue, and blood is the most important problem in the BNCT (Cheng et al, 2022; Sauerwein et al, 2021). Currently, despite the development of new targeted boron delivery drugs, only second‐generation boron drugs, such as boronophenylalanine and sodium borocaptate, are being used in clinical trials (Barth et al, 2018; Dymova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In particu-lar, glioblastoma is an aggressive malignant brain tumor, characterized by rapid and invasive growth that remains almost incurable. To date, there have been a number of examples of the successful use of BNCT for the treatment of brain tumors in clinics [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, none of them has yet been approved for clinical applications. The only boron-containing drugs now used for BNCT in clinics are based on boronophenylalanine (such as Steboronine ® from Stella Pharma [8]) or sodium borocaptate [2]. These compounds cannot be precisely addressed to the tumor, and their pharmacokinetics and biodistribution are not optimal, so their tumor uptake is characterized by significant variability [9].…”
Section: Introductionmentioning
confidence: 99%